2018
DOI: 10.1161/circinterventions.118.006832
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Brachytherapy for the Management of Repeated Multimetal-Layered Drug-Eluting Coronary Stent Restenosis

Abstract: Background: Because of the widespread acceptance of percutaneous coronary intervention with drug-eluting stents as an effective treatment strategy for in-stent restenosis, it is common to encounter multimetal layer stent restenosis in the recent years. This study aimed to evaluate the clinical outcomes of such patients treated with intravascular brachytherapy (IVBT) in comparison with other percutaneous options. Methods and Results: We en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
2
31
1
Order By: Relevance
“…In contrast to the study by Yabushita et al 28 (Table S10). [8][9][10] Our results are consistent with the outcomes of those studies with an incidence of target lesion/vessel revascularization of 30-40% at 2-3 years, highlighting the high risk of repeat failure after VBT. We also found that the initial presentation with ACS was independently associated with TLF.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In contrast to the study by Yabushita et al 28 (Table S10). [8][9][10] Our results are consistent with the outcomes of those studies with an incidence of target lesion/vessel revascularization of 30-40% at 2-3 years, highlighting the high risk of repeat failure after VBT. We also found that the initial presentation with ACS was independently associated with TLF.…”
Section: Discussionsupporting
confidence: 89%
“…Varghese et al demonstrated that using VBT in recurrent DES‐ISR was associated with lower major adverse cardiac events compared with other therapies at 1 year 10 . Despite the classic description of focal restenosis with DES‐ISR, a higher percentage of recurrent DES‐ISR lesions had diffuse ISR as described in our cohort and by Mangione et al 8 …”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Varghese et al . [17] reported that in patients with recurrent DES-ISR treated by new-generation DES repeat deployment, the rates of 1-year MACE and TLR were 30.8% and 24.2%, respectively. These were similar to the adverse event rates for the Re-DES group in our study.…”
Section: Discussionmentioning
confidence: 99%